Global change explains reduced seeding in a widespread New Zealand tree: indigenous Tūhoe knowledge informs mechanistic analysis - Yukich Clendon, Oscar M. M.; Carpenter, Joanna K.; Kelly, Dave; Timoti, Puke; Burns, Bruce R.; Boswijk, Gretel; Monks, Adrian (Frontiers in Forests and Global Change, 2023)
Climate change is expected to exacerbate the pressures faced by already fragile ecosystems. Negative impacts on the localized and culturally significant plant and animal species within these ecosystems will have flow oncascading effects for the integrity of indigenous communities that interact with those species. Understanding how climate change affects culturally important seed crops may be particularly important, as seeds are critical for forest regeneration as well as providing sustenance for wildlife and people. In the central North Island/Te Ika-a-Māui of Aotearoa-New Zealand, Tūhoe elders of the Tuawhenua region have observed declines in seed production by the large-fruited locally dominant forest tree Beilschmiedia tawa (tawa, Lauraceae) over the last half century, which could be related to climate change. We used seed trap data from six sites throughout the geographic range of tawa to measure trends in seed crop size from 1986 to 2020 and to determine which weather factors affect seed crops. We then used these weather predictors to hindcast how tawa seeding may have changed in Tuawhenua forests from 1910-2019, based on historic weather data. Seed trap data showed a decline in seeding through time Aacross tawa's range, seeding was significantly lower in later years and that seeding was lower at more northerly sites. Seed crops were synchronous between among trees within a sitewithin sites, but unusually were strongly asynchronous between among sites. High seed crops were associated with cooler summer and winter temperatures, and with high rainfall. In the Tuawhenua region, increases in summer and winter temperatures appear to have contributed to the declines in tawa seed crops observed by elders, with the model predicting that years with heavy fruiting have become less frequent after 1940.